The Effect Of Customer Satisfaction Levels And Prices On The Comfort Of The Place At Fore Coffe Shop Surabaya - liling listyawati; Irma Romauli Sinaga; Damajanti Sri Lestari (GLOBAL SCIENTS PUBLISHER, 2026)
This research is oriented to test and analyze how the impact of customer satisfaction and price on the comfort of the place at the FORE Puri Widya Kencana Coffee Shop outlet in Surabaya. By applying an associative-causal quantitative design, this study recruited 96 respondents as a sample whose calculation was based on the Cochran formula, while the determination was made using the purposive sampling method. Primary data collection was carried out through the distribution of questionnaires with a 5-point Likert scale, which was then processed through the multiple linear regression method based on SPSS software. Based on the evaluation of the instrument, all question items are confirmed to be valid and reliable. The regression model was also declared to have passed the classical assumption test because it was normally distributed and free from indications of multicollinearity. From the processing results, a structural model was obtained. Partial testing (t-test) showed that the level of customer satisfaction contributed positively and significantly to the comfort of the place (; sig. = 0.000), as well as the price factor (sig. = 0.000). Simultaneously (test F), the two independent variables were shown to have a meaningful simultaneous influence (; sig. = 0.000), which means that the criteria for acceptance of hypotheses H1, H2, and H3 have been met. The determination number ( R Square) of 0.561 indicates that the variability of place comfort can be described by customer satisfaction and price of 56.1%, while the remaining 43.9% is determined by other determinants that are outside the scope of this research. This conclusion indicates that optimizing customer satisfaction and ideal pricing policies are crucial instruments in strengthening the perception of physical comfort in the coffee shop business.